Cost effectiveness of primary stroke prevention in atrial fibrillation: Swedish national perspective. Issue 6867 (12th December 1992) - Gustafsson, C.; Asplund, K.; Britton, M.; Norrving, B.; Olsson, B.; Marké, L. A.
Abstract : OBJECTIVE--To assess the potential effects of primary prevention with anticoagulants or aspirin in atrial fibrillation on Swedish population. DESIGN--Analysis of cost effectiveness based on the following assumptions: about 83, 000 people have atrial fibrillation in Sweden, of whom 22, 000 would be potential candidates for treatment with anticoagulants and 55, 000 for aspirin treatment; the annual 5% stroke rate is reduced by 64% (with anticoagulants) and 25% (with aspirin); incidence of intracranial haemorrhage of 0.3%, 1.3%, or 2.0% per year; direct and indirect costs of a stroke of Kr180, 000 and Kr90, 000; estimated annual cost of treatment is Kr5030 for anticoagulants and Kr100 for aspirin. SETTING--Total Swedish population. MAIN OUTCOME MEASURES--Direct and indirect costs of stroke saved, number of strokes prevented, and cost of preventive treatment. RESULTS--Depending on the rate of haemorrhagic complications 34 to 83 patients would need to be treated annually with anticoagulants to prevent one stroke; 83 patients would need to be treated with aspirin. Giving anticoagulant treatment only would reduce costs by Kr60 million if the incidence of intracranial haemorrhage were 0.3% but would imply a net expense if the complication rate exceeded 1.3%. The total savings from giving anticoagulant (22, 000 patients) and aspirin (55, 000 patients) treatment would be Kr175 million per year corresponding to 2 million pounds per million inhabitants each year. CONCLUSIONS--Treatment with anticoagulants and, if contraindications exist, with aspirin is cost effective provided that the risk of serious haemorrhage complications due to anticoagulants is kept low.